Martial, Book VII : a commentary - Galán Vioque, Guillermo. (Mnemosyne, Supplements, 2002)
This volume is the first comprehensive commentary on the seventh book of Martial's epigrams. The introduction discusses the date of publication of Martial's books, the themes of the epigrams of book seven as well as the transmission of the text. The autor pays special attention to the adulation of Domitian in book seven, the satirization of lawyers, legacy-hunters, parasites and dinner-guests, and hetero- and homosexuality. The commentary, preceded by a revised edition of Shackleton Bailey's Teubner edition (1990), focuses on literary, linguistic and metrical matters. Thematic relationships with other books of Martial and other Greek and Latin literature are highlighted. Attention is also paid to the use of recurrent motifs, obscene language, puns, double meanings and proper names.